Combined therapeutic option for NDM-producing Serratia Marcescens – an in vitro study from clinical samples - Balbina Chilombo Albano; Leticia Ramos Dantas; Gabriel Burato Ortis; Paula Hansen Suss; Felipe Francisco Tuon (Brazilian Journal of Infectious Diseases)
Background: Treating NDM-producing bacteria poses a significant challenge, especially for those bacteria inherently resistant to polymyxin, such as Serratia marcescens, necessitating combined therapies. Objective: To assess in vitro the synergistic effect of different antimicrobial combinations against NDM-producing S. marcescens. Methods: Four clinical isolates were tested with various antibiotic combinations: polymyxin, amikacin, meropenem, and aztreonam. Concentrations used were those maximized by pharmacokinetic and pharmacodynamic assessments. Synergy evaluation involved a static macrodilution test followed by a time-kill curve assay. Results: All four isolates demonstrated resistance according to CLSI and EUCAST standards for the tested antibiotics (polymyxin, amikacin, meropenem, and aztreonam). In the macrodilution synergy test, the combination of aztreonam and amikacin was active in 2 out of 4 isolates within 24 h, and polymyxin with meropenem in only one isolate, despite of intrinsic resistance to polymyxin. However, time-kill curve analysis revealed no synergism or additive effect for combinations with the tested antimicrobials. Conclusion: Combinations of polymyxin, meropenem, aztreonam, and amikacin at doses optimized by pharmacokinetic/pharmacodynamic were insufficient to demonstrate any synergism in NDM-producing S. marcescens isolates in time-kill curves.